Smart sejadah - Abdul Malek, Mal-Khairul Amir; Zakaria, Normah; Hamzah, Norhasyimah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida (Penerbit UTHM, 2020)
The Smart Sejadah is a device that can count the number of rakaat in prayers. This product can help to reduce the problem of forgetting number rakaat in prayers. This product will produce the output at every time the prostration is performed in the prayer. Two times of the prostration will produce one rakaat and the amount of rakaat will increase at every two times the prostration movement is done. Determination of components in the circuit will be performed and drawn using the Proteus 8 Professional software. This study was focused for the adults aged 30 years and above to assist in fulfilling their prayers. Methodology selected for implementing this project using the Design Thinking Process model. The push plate switch is used as a signal probe for the prostration movement and the seven segment display is used to display the number of rakaat in the prayer. The Arduino Wemos D1 Micro controller is used to control the entire circuit. As a result of this project, it was achievied the desired output. In conclusion, this product can help the adults aged 30 years and above who often face the problem of forgetting number rakaat in prayers besides, can improve the quality of their prayers.